PENGEMBANGAN MEDIA ANIMASI BERBANTU POWTOON PADA PEMBELAJARAN BAHASA INDONESIA - Nurul Aina Fika (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
The development of animation media assisted by powtoon in learning Indonesian poetry material is motivated by the low interest and motivation of students during the learning process due to the lack of variety of learning media. This study aims to produce animation learning media with the help of powtoon in learning Indonesian poetry material and see its feasibility. Product development in this study uses a 4-D learning development model. The 4-D development model was developed by Thagarajan et al, where this model consists of four main stages starting from defining, planning (designing), developing (developing), and disseminating (disseminate) (Trianto, 2017:82). This method and model was chosen because it aims to produce animation media products with the help of Powtoon in Indonesian language learning. The subject of the trial was a Class IV teacher who was at UPT SD Negeri 18 Lalang with poetry material. The object of this research is animation media which is assisted by Powtoon. This study uses a questionnaire as a tool to test the feasibility of Powtoon-assisted animation media through validation of material experts, media experts and teacher responses. Based on the analysis of the results of the research and discussion, it can be concluded that in the validation of material and media experts which was carried out in two stages with one revision, the animation assisted Powtoon media in Indonesian language learning developed was declared good and feasible to be used as learning media at UPT SD Negeri18 weeds. This can be proven by the assessment obtained from the initial product with the revised product experiencing an increase in assessment. Thus the use of animation media can increase students' interest and motivation and become a learning innovation for students.